Evolution of Internal Stresses During Cyclic Superelastic Deformation of NiTi Investigated by X-ray Synchrotron Diffraction. (2015) - Sedmak, P.; Sittner, P.; Pilch, J.; Curfs, C.
Abstract: Cyclic tensile superelastic deformation of NiTi was investigated using high resolution in-situ synchrotron x-ray diffraction method. Diffraction patterns were recorded under applied stress prior and after the stress induced martensitic transformation, analyzed and interpreted in view of the evolution of microstructure in the transforming polycrystal. A simple bicrystal scheme of the polycrystal transformation is used to rationalize the experimental evidence on microstructure evolution during cycling. It is claimed that the instability of cyclic superelastic response of NiTi is due to the gradual rise of internal stresses originating from the accumulation of plastic deformation accompanying the martensitic transformation in constrained polycrystalline environment.